2021
DOI: 10.1038/s41390-021-01546-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic methods for neonatal hyperbilirubinemia: benefits, limitations, requirements, and novel developments

Abstract: Invasive bilirubin measurements remain the gold standard for the diagnosis and treatment of infants with severe neonatal hyperbilirubinemia. The present paper describes different methods currently available to assess hyperbilirubinemia in newborn infants. Novel point-of-care bilirubin measurement methods, such as the BiliSpec and the Bilistick, would benefit many newborn infants, especially in low-income and middle-income countries where the access to costly multi-analyzer in vitro diagnostic instruments is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Analysis of bilirubin in clinical laboratories is performed by automated methods 4 . For highly sensitive analysis of bilirubin in complex biological matrices, a number of other analytical methods have been introduced, based on HPLC and coupled with advanced detectors, various sensors, molecularly imprinted surfaces, or the uorescent bilirubin-binding protein UnaG 5-7 .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of bilirubin in clinical laboratories is performed by automated methods 4 . For highly sensitive analysis of bilirubin in complex biological matrices, a number of other analytical methods have been introduced, based on HPLC and coupled with advanced detectors, various sensors, molecularly imprinted surfaces, or the uorescent bilirubin-binding protein UnaG 5-7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although most forms of jaundice are physiological and self-limiting, severe cases will result in overwhelming bilirubin deposition in the brain without timely treatment, leading to irreversible neurological damage, namely, kernicterus ( 1 , 2 ). Bilirubin measurements are fundamental for diagnosis, risk stratification, and treatment decision-making in cases of neonatal hyperbilirubinemia ( 3 ). The initiation of phototherapy for neonates with severe hyperbilirubinemia or at high risk of subsequent severe hyperbilirubinemia is commonly assessed using a combination of risk factors evaluation and the Bhutani’s hour-specific bilirubin nomogram, which was established on the basis of total serum bilirubin (TSB) measurements obtained by the diazo method ( 1 , 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the technology underlying bilirubin assays has evolved significantly. New methods such as trace sample-based blood gas bilirubin measurements performed by Co-oximetry now provide more choices and convenience for clinicians ( 3 ). Blood gas analyzers such as the Roche Cobas models support multi-test panels and deliver test results quickly; consequently, they are commonly used in neonatal intensive care units (NICUs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on BR levels estimation have been reported [7,8], but these techniques suffer from the instrument complexity and cost. This mini-paper investigated the dualwavelength (DWL) technique for BR estimation using a system-on-chip (SoC).…”
Section: Introductionmentioning
confidence: 99%